Análisis comparativos de las amenazas informáticas suscitadas a los sitios web de las entidades del sistema financiero. - Avegno Tenorio, Paulina Evelina (2023)
The financial system comprises a set of institutions, markets and instruments that are responsible for financial intermediation, i.e., collecting economic resources and then directing them towards the financing of business activities, projects and other economic initiatives. Currently, the websites of financial institutions have improved significantly in terms of security and functionality, requiring an optimal user experience and greater protection of the customer's personal information. However, the increase in online financial activity has led to an increase in cyber-attacks against these entities, putting customer privacy at risk. Financial institutions are exposed to a variety of IT threats that can affect the security of their systems and jeopardize the confidentiality, integrity and availability of their clients' information. Some of the most common threats include: Phishing attacks, Malware, Brute force attacks.